2019
DOI: 10.20944/preprints201908.0059.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Effect of Recreation in a Snow-Covered Forest Environment on the Psychological Relaxation of Young Females

Abstract: Forest recreation can be successfully conducted for the purpose of psychological relaxation, as has been proven in previous scientific studies. During the winter in many countries, when snow cover occurs frequently, forest recreation (walking, relaxation, photography, etc.) is common. Nevertheless, whether forest therapy conducted in a forest environment with a snow cover will also have a positive effect on psychological indicators remains unknown. Furthermore, male subjects frequently participate in forest th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…The influence of season on health is investigated in just one study, where simple exposure to a broadleaved forest revealed better psychological restorative effects during the winter than in springtime [125]. Other studies, although not directly aimed at comparing seasonal effects on health, confirmed a substantial emotional, restorative, and vitalizing effect on the participants by visiting forests during winter with snow [126,127], during autumn [128,129] and during spring, also activating physiological relaxation [130]. Joung et al [129] confirmed wellbeing effects of looking at a forest landscape (rather than an urban one) from the top of a building during autumn.…”
Section: Forest Featuresmentioning
confidence: 99%
“…The influence of season on health is investigated in just one study, where simple exposure to a broadleaved forest revealed better psychological restorative effects during the winter than in springtime [125]. Other studies, although not directly aimed at comparing seasonal effects on health, confirmed a substantial emotional, restorative, and vitalizing effect on the participants by visiting forests during winter with snow [126,127], during autumn [128,129] and during spring, also activating physiological relaxation [130]. Joung et al [129] confirmed wellbeing effects of looking at a forest landscape (rather than an urban one) from the top of a building during autumn.…”
Section: Forest Featuresmentioning
confidence: 99%